ANTHRACNOSE RESISTANCE GENE2 confers fungal resistance in sorghum. (18th December 2022) - Mewa, Demeke B.; Lee, Sanghun; Liao, Chao‐Jan; Adeyanju, Adedayo; Helm, Matthew; Lisch, Damon; Mengiste, Tesfaye
SUMMARY: Sorghum is an important food and feed crop globally; its production is hampered by anthracnose disease caused by the fungal pathogen Colletotrichum sublineola ( Cs ). Here, we report identification and characterization of ANTHRACNOSE RESISTANCE GENE 2 ( ARG2 ) encoding a nucleotide‐binding leucine‐rich repeat (NLR) protein that confers race‐specific resistance to Cs strains. ARG2 is one of a cluster of several NLR genes initially identified in the sorghum differential line SC328C that is resistant to some Cs strains. This cluster shows structural and copy number variations in different sorghum genotypes. Different sorghum lines carrying independent ARG2 alleles provided the genetic validation for the identity of the ARG2 gene. ARG2 expression is induced by Cs, and chitin induces ARG2 expression in resistant but not in susceptible lines. ARG2‐mediated resistance is accompanied by higher expression of defense and secondary metabolite genes at early stages of infection, and anthocyanin and zeatin metabolisms are upregulated in resistant plants. Interestingly, ARG2 localizes to the plasma membrane when transiently expressed in Nicotiana benthamiana . Importantly, ARG2 plants produced higher shoot dry matter than near‐isogenic lines carrying the susceptible allele suggesting an absence of an ARG2 associated growth trade‐off. Furthermore, ARG2‐mediated resistance is stable at a wide range of temperatures. Our observations open avenues for resistance breeding and for dissecting mechanisms of resistance. Significance Statement: Sorghum is a crop of global importance that is used for food, feed and biofuel. The crop feeds millions of people, especially small holder framers around the world. The productivity of sorghum is constrained by anthracnose diseases caused by the fungus Colletotrichum sublineola . Genetic resistance provides the most sustainable disease control method. We identified and characterized a sorghum anthracnose resistance gene encoding a nucleotide‐binding leucine‐rich repeat protein by exploring natural variation in the crop. Our findings will have significant implications for improvement of disease resistance in sorghum, as well as for future studies in the molecular genetics of pathogen resistance.